Addressing Differential Attainment Among International Medical Graduates - Taha Anjum; Subha Thiyagesh; Rajarshi Das (BJPsych Open)
Aims: The aim of this project was to gain a better understanding of clinical and professional areas that international medical graduates find difficult and often these areas can be a barrier in further career progression. This project was undertaken as part of the Leadership and Management Fellow Scheme organised by the Royal College of Psychiatrists. The idea was to align the learnings to broader goals at organisational level.